Tipologi Dan Morfologi Rumah Tinggal Etnis Tionghoa Peranakan Di Desa Pasongsongan, Sumenep - Cipta, Resty Linandi; Wulandari, Lisa Dwi; Antariksa, Antariksa (RUAS, 2015)
The purpose of this study is to analyze typhology of half blood Chinese ethnic house by classifying the house element based on certain types, in order to obtain the thypology from micro side which is seen from roof thypology, column, floor, balustrade, console and the elements of openings in the form of doors, windows, bouvenlicht. Morphology from the micro side by analyzing the changes which is related with residential home element, meso by analyzing the changes and addition of sketch which is seen from space organization so the effect on changes in function, hierarchy, and circulation in the room. The existence of acculturation causing the Java style influence, China and the Netherlands in this house. The method used in this study is a qualitative descriptive by analyzing the physical condition of both residential and layout elements that can be produced by the characteristics of each typology and morphological findings.Key Word : Typology, morphology, the half blood Chinese ethnic